The Processing of Steamed Cassava Brownies as an Enhancement of the Knowledge and Skills of the People of Suka Menang Village - Adhriko Setiawan; Jumti Jaduri; Nabila Sherendita; Berliana M Pardede; Lolita M Nainggolan; Afifah P Kinanti; Asty Ananda; Gusti Prayoga; Feby Juniansyah; Sukery Jaya; M Rizky Dwi Putra; Ahmad Rizki; Merynda Indriyani Syafutri; Fidel Harmanda Prima; Lauren F Manalu; Ela Roswasti Angelia Syeba Ginting; M Auliya Nabhan (Universitas Lambung Mangkurat, 2024)
Cassava is one of the food commodities grown in Suka Menang Village. The people of Suka Menang Village only sell fresh cassava and process it into daily foods such as boiled and fried cassava. Cassava also has the potential to be used as raw material for steamed brownies. Steamed cassava brownies do not use wheat flour, which is the advantage of steamed cassava brownies. This activity aimed to introduce steamed cassava brownies and to increase the Suka Menang Village community's knowledge of the processing technology of steamed cassava brownies. The target audience was the community of Suka Menang Village. The method used was Community Based Participatory Research (CBPR). The activity consisted of 2 stages: 1) a hedonic test of steamed brownies products, and 2)socialization of the potential of cassava and cassava steamed brownies processing and the practice of cassava steamed brownies processing. The results showed that cassava could be processed into steamed brownies. Based on the sensory properties test, the steamed cassava brownies were preferred and acceptable. In addition, there was an increase in the target audience's understanding of the material presented, which was 12.87%. Through this activity, the people of Suka Menang Village had skills in processing cassava-steamed brownies.